Estimation of Transmission Mechanism of Monetary Policy in Serbia - Bungin, Sanja; Reljić, Marija; Ivković, Bojana (Industrija, 2015)
Abstract: Transmission mechanism of monetary policy recently has been subject to several studies in Serbia. The so called “black box” of monetary policy is investigated with aim to identify the effects of transmission channel in environment where exchange rate has dominant role in central bank operations. Therefore, it is a challenge to approach this problem in inflation targeting regime where is expected to prevail key interest rate as main policy instrument. Study employs unrestricted Vector Autoregression model to estimate significance of exchange rate and interest rate channel. As expected, exchange rate has far more stronger influence on inflation, even though there are some signs of interest rate channel existence. Introducing Euribor as endogenous variables in VAR system displayed important impact on real variables.
Keywords: Serbia; Inflation targeting; Inflation; Monetary Policy; Interest Rate; Exchange rate